2011
DOI: 10.4049/jimmunol.1002691
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 Attenuates Collagen-Induced Arthritis by Modulating the Development of Foxp3+ Regulatory T Cells

Abstract: IL-3, a cytokine secreted by Th cells, functions as a link between the immune and the hematopoietic system. We previously demonstrated the potent inhibitory role of IL-3 on osteoclastogenesis, pathological bone resorption, and inflammatory arthritis. In this study, we investigated the novel role of IL-3 in development of regulatory T (Treg) cells. We found that IL-3 in a dose-dependent manner increases the percentage of Foxp3+ Treg cells indirectly through secretion of IL-2 by non-Treg cells. These IL-3–expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 43 publications
(33 reference statements)
6
48
0
Order By: Relevance
“…In addition, they induce expression of MMPs, which degrade cartilage matrix, thereby aggravating the degeneration of joints (15). We have previously shown that IL-3 is a potent inhibitor of osteoclast formation and pathological bone resorption in vitro (17)(18)(19)(20), and it protects cartilage and bone damage in murine models of inflammatory arthritis (20) and collagen-induced arthritis (21). In this study, we investigated the role of IL-3 in regulation of chondrocyte function in vitro and cartilage degradation in vivo in a mouse model of human OA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they induce expression of MMPs, which degrade cartilage matrix, thereby aggravating the degeneration of joints (15). We have previously shown that IL-3 is a potent inhibitor of osteoclast formation and pathological bone resorption in vitro (17)(18)(19)(20), and it protects cartilage and bone damage in murine models of inflammatory arthritis (20) and collagen-induced arthritis (21). In this study, we investigated the role of IL-3 in regulation of chondrocyte function in vitro and cartilage degradation in vivo in a mouse model of human OA.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity receptor for IL-3 consists of a heterodimer of IL-3-specific a-chain and a common b-chain, which is shared with GM-CSF and IL-5 (33). IL-3Ra is expressed by human hematopoietic stem cells (34), endothelial cells and monocytes (35), activated T cells (21), osteoclasts (17)(18)(19), osteoblasts, and MSCs (36). In this study, we report for the first time, to our knowledge, that both mouse and human chondrocytes express IL-3Ra at transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(6). Using a disease-specific animal model of human RA, we showed that IL-3 significantly increases the percentage of Foxp3 1 functional Treg cells in both in vitro and in vivo conditions (7).…”
mentioning
confidence: 93%